Antecedents of consumer ethnocentrism - Albarq, Abbas; Nik Mat, Nik Kamariah (2007)
This study attempts to validate the antecedents of consumer ethnocentrism and determine causal relationships between the specified antecedents and customer ethnocentrism in light of customer behavior in a less developed country Jordan. Seven antecedents were identified: culture openness, conservatism, collectivism, patriotism, control belief, interest in foreign travel and attitude toward foreign product. Each variable is measured by a 7-point Likert-scale of various developed past scales. Consumer ethnocentrism was measured using the CETSCALE 17 items. An 84 percent response rate was collected from 120 questionnaires distributed. Confirmatory factor analysis performed on the data reveals that the measurement model and structural model are statistically fit. Structural equation modeling (SEM) analysis establishes causal relationships between cultural openness, control belief, foreign travel, attitude and ethnocentrism.